Psychosocial service use and unmet need among recently diagnosed adolescent and young adult cancer patients. Issue 1 (28th June 2012) - Zebrack, Brad J.; Block, Rebecca; Hayes‐Lattin, Brandon; Embry, Leanne; Aguilar, Christine; Meeske, Kathleen A.; Li, Yun; Butler, Melissa; Cole, Steven
Abstract BACKGROUND: Adolescents and young adults (AYAs) with cancer demonstrate biomedical risks and psychosocial issues distinct from those of children or older adults. In this study, the authors examined and compared the extent to which AYAs treated in pediatric or adult oncology settings reported use of, and unmet need for, psychosocial support services. METHODS: Within 4 months of initial cancer diagnosis, 215 AYAs ages 14 to 39 years (99 from pediatric care settings and 116 from adult care settings; 75% response rate) were assessed for reporting use of information resources, emotional support services, and practical support services. Statistical analyses derived odds ratios and 95% confidence intervals for service use and unmet needs after controlling for race, employment/school status, sex, relationship status, severity of cancer, treatment, and treatment‐related side effects. RESULTS: AYAs ages 20 to 29 years were significantly less likely than teens and older patients ages 30 to 39 years to report using professional mental health services and were significantly more likely to report an unmet need with regard to cancer information, infertility information, and diet/nutrition information. Compared with teens who were treated in pediatric facilities, AYAs who were treated in adult facilities were more likely to report an unmet need for age‐appropriate Internet sites, professional mental health services, camp/retreats programs, transportation assistance, and complementary and alternative health services. CONCLUSIONS: Substantial proportions of AYAs are not getting their psychosocial care needs met. Bolstering psychosocial support staff and patient referral to community‐based social service agencies and reputable Internet resources may enhance care and improve quality of life for AYAs. Cancer 2013. © 2012 American Cancer Society.